Aspectos nutricionais de um sistema agroflorestal com eucalipto no sul do Rio Grande do Sul, Brasil - Calil, Francine Neves (2008)
This study was conducted at an experimental area at Aroeira Farm, belonging to Votorantim Celulose e Papel company, under the geographic coordinates 31° 45 50.7 S e 53° 50 34.9 W, located in Candiota county. In the area there is an experimental field, where some production factors involved in an agroflorestry system are being monitored, with four different treatments (T 1 = eucalyptus planted in 3 m x 2 m spacing; T2= native grass; T3 agroforestry system planted in double line and T4 agroforestry system planted in triple line). Because of this, this study was divided in four chapters, that are: 1) Biomass and nutrients in the agroforestry components in the south of Rio Grande do Sul, Brazil, where the above ground biomass from eucalyptus, sorghum and sunflower was quantified, as well as the nutrients in it. As above ground biomass, sorghum showed a total of 9.876 kg ha-1 (17,67% in the leaves, 47,74% in the stem and 34,61% in grains. In sunflower, the total biomass above the gound was 11.968 kg ha-1 (21,62% in blossom, 24,03% in the leaves, 21,32% in grains and 22,03% in the stem). Eucalyptus total above ground biomass totalized 10.974 kg ha-1 (45,28% in wood, 26,31% in branches, 19,96% in leaves and 8,45% in bark). The total amount of nutrients in sorghum followed this magnitude for total: C > N > K > Ca > P > Mg > S > Fe > Al > Na > Mn. In sunflower the total amount followed this magnitude: C > K > N > Ca > Mg > P > S > Na > Fe > Al > Mn. In eucalyptus the magnitude for total was: C > N > Ca > K > Mg > P > S > Na > Mn > Al > Fe; 2) Inputs through precipitation in área in south Rio Grande do Sul, Brazil, where in native grass area are installed 10 plastic rain gauges (23 cm of diameter). The volume quantification as well as the composed sampling collections for pH, electrical conductivity, nitrate, nitrite, ammonium, phosphorus, sulphur, chlorine, calcium, magnesium, potassium and calcium analysis were collected every fifteen days. The total precipitation during the studied period was 1.605,79 mm, being 13, 56% higher than the average for the region (from September, 3006 to August, 2007). The average pH was 6,59, being the lowest value as 5,66 and this is not considered as acid rain. The average electrical conductivity was 52,84. Sodium showed an average concentration of 2,52 mg/L; potassium 1,07 mg/L; calcium 1,15 mg/L; magnesium 0,17 mg/L; nitrate 0,13 mg/L of N; nitrite 0,52 mg/L of N; ammonium 1,14 mg/L of N; phosphorus 0,66 mg/L; sulphur 0, 19 mg/L, and chlorine 1,60 mg/L. The input through rain precipitation followed this magnitude: Na > Cl > N > K > Ca > S > P >Mg; 3) Soil solution chemical characteristics in an agroforestry system in south Rio Grande do Sul, where the objective was to chemically evaluate the soil solution, in two differend depths (30 cm and 80 cm), in four different treatments )T1 = eucalyptus planted in 3 m x 2 m spacing; T2= native grass; T3 agroforestry system planted in double line and T4 agroforestry system planted in triple line). For sampling collections, lisimeters were used (8 in each depth and in each treatment), accionated by vacuum pumps (through timers), every four hours, kept turned on for 10 minutes. The soil solution samples were collected every fifteen days and sent to pH, electrical conductivity, nitrate, nitrite, ammonium, phosphorus, sulphur, chlorine, calcium, magnesium, potassium and calcium analysis. Soil solution behavior, in different depths and different treatments, showed to be highly variable, considering the kind of crop involved; 4) This chapter had as objective to demonstrate a partial summary from the biogeochemical in the agroforestry system studied, showing the macronutrients distribution in above ground biomass and in the soil. For this, as inputs, it was considered the rain and dust and also fertilizations done for sorghum, sunflower and eucalyptus. Through a scheme, al the fraction and parts that would be evaluated in these system during the 7 years of this study. The calculations were based on the water precipitation samples and on vegetal tissues analysis; for soil calculations it was used the soil analysis. In this study it was possible to quantify the macronutrients inputs and its absorption through the crops and also the amounts of these nutrients in soil; next year it is going to be possible to quantify the nutrients inputs through stem flow, internal precipitation and litter. The runoff is also going to be calculated through soil solution samples collected through lisimeters already installed in the field The inputs of nitrogen totalized 179, 76 kg ha-1 through precipitation and fertilization; phosphorus totalized 74, 31 kg ha-1 through precipitation and fertilization, potassium through precipitation and fertilization totalized 79, 37 kg ha-1 ,calcium 14,12 kg ha-1 and magnesium 2,09 kg ha-1. Soil had 432, 49 kg ha-1 of nitrogen, 63,61 kg ha-1 of phosphorus, 1.656 kg ha-1 of potassium, 65.250 kg ha-1 of calcium and 5.439,60 kg ha-1magnesium.